2003
DOI: 10.1177/0963662503012001413
|View full text |Cite
|
Sign up to set email alerts
|

Big science, little news: science coverage in the Italian daily press, 1946-1997

Abstract: This article reports on a content analysis of science coverage by the leading Italian newspaper, Il Corriere della Sera, over a period of fifty years. Results show an expansion of such coverage over time, although it was increasingly “institutionalized” in new sections devoted to science and medicine. The typical science story can be described as dealing with biomedical issues, referring to a geographical context outside Italy, relying on uncontested scientific expertise and presenting the consequences of scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0
21

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 15 publications
5
58
0
21
Order By: Relevance
“…3 For this particular study, all the stories published in the science section in the month of April 2004 were analyzed in the following newspapers: La Nación, of Argentina; El Mercurio, of Chile; Reforma, of Mexico; El Comercio, of Ecuador; O Globo, Folha de São Paulo and Jornal do Commercio/Pernambuco, from Brazil. One of the criteria for selection of the newspapers was to have a science editor and staff focused on the area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 For this particular study, all the stories published in the science section in the month of April 2004 were analyzed in the following newspapers: La Nación, of Argentina; El Mercurio, of Chile; Reforma, of Mexico; El Comercio, of Ecuador; O Globo, Folha de São Paulo and Jornal do Commercio/Pernambuco, from Brazil. One of the criteria for selection of the newspapers was to have a science editor and staff focused on the area.…”
Section: Methodsmentioning
confidence: 99%
“…In the international context, various studies are identified on the coverage of matters of science and technology in daily newspapers (see, for example: [17], [5], [16], [4] in the United States, [7], [22] in Canada; [18] in Germany, [10], [2], [11] in the United Kingdom, [3] in Italy, [6] in India, only to cite a few).…”
Section: Introductionmentioning
confidence: 99%
“…Sobre medicina e saúde, particularmente, estudos realizados no Reino Unido (Durant, Evans, Thomas, 1992), Canadá (Einsiedel, 1992) e Itália (Bucchi, Mazzolini, 2003) já demonstraram que tal área domina o imaginário social do público no que diz respeito à ciência e constitui, assim, uma área paradigmática da ciência em geral, fenômeno que foi denominado por Bauer (1998) "medicalização das notícias de ciência". Além disso, medicina e saúde formam um campo da ciência no qual o público consegue perceber uma relação direta com seu cotidiano (León, 2008).…”
Section: Gráfico 1: Proporção De Matérias De Candt Veiculadas Pelos Telunclassified
“…Nos EUA e na Europa, há vários estudos que se dedicam a analisar como a mídia -sobretudo jornais impressos e TV -aborda temas de C&T (alguns exemplos são: Bucchi, Mazzolini, 2003;Hijmans, Plejter, Wester, 2003;Pellechia, 1997;Bauer, Ragnarsdóttir, Rúdólfsdóttir, 1993;Hansen, Dickinson, 1992). Alguns trabalhos abordam a questão de forma comparativa entre países (Lehmkuhl et al, 2012;Verhoeven, 2010;León, 2008;Göpfert, 1996).…”
unclassified
See 1 more Smart Citation